Unemployment reduction or labor force expansion? How partisanship matters for the design of active labor market policy in Europe. (26th April 2017) - Cronert, Axel
Abstract: Comparative scholars fundamentally disagree about the impact of partisan politics in modern welfare states, particularly in certain 'new' policy areas such as active labor market policy (ALMP). Using new data on 900 ALMP programs across Europe, this study attempts to reconcile a long-standing dispute between the traditional 'power resources' approach and the 'insider/outsider' approach pioneered by Rueda. The study argues that both left-wing and right-wing governments invest in ALMP but that politics still matter because parties' preferences regarding unemployment differ. The left is more inclined to expand programs primarily designed to reduce unemployment, which exclusively target 'core' groups in, or at risk of, unemployment, and programs in which participants are no longer counted among the unemployed. In contrast, both sides are equally prone to expand programs that also—or instead—target people who are not yet participating in the labor market, which thus also—or instead—serve to increase labor supply.